A critical review on molecular dynamics applied to structure fracture and failure analysis. (May 2023) - Wang, Mengmeng; Incecik, Atilla; Yang, Chunsheng; Gupta, Munish Kumar; Królczyk, Grzegorz; Andriukaitis, Darius; Li, Z.
Abstract: Due to the continuous exploration of ocean resources, the marine structures are gradually applied from offshore to far-reaching sea areas, and the safety and reliability of the marine structures are becoming more and more important. Fractures and failures of the marine structures are the most common structural damages while considerable numerical computational techniques are developed to investigate the failure mechanisms and health monitoring of the marine structures. This review aims to report the numerical methods for structural failure analysis from macroscopic, mesoscopic to microscopic scales, including the methods of the macroscopic continuum, lattice Boltzmann, and molecular dynamics. The fundamental theories and recent progresses in the macroscale, mesoscale and microscale are summarized to suggest the future development directions. The discussions of the latest achievements in structural failure analysis will not only deepen the understanding of the structural failure mechanisms subject to solid-fluid coupling in a marine environment, but also provide necessary guidance for engineers and researchers in this research field.